The impact of agricultural loans on the technical efficiency of rice farmers in the upper north of Thailand - Chaovanapoonphol Y. (2014)
Rice is the major crop in Thailand and it will remain so as long as it continues to be the major export crop and the staple food of the Thai population. However, the fact is that, although Thailand is the main rice-exporting country in the world, its rice yields are among the lowest in Asia (Office of Agricultural Economics, 2004a, b). This might imply low productivity and high technical inefficiency in major rice production. In an attempt to resolve this problem, the Thai government has promoted the use of inputs in rice production, such as chemical fertiliser, highyielding varieties and chemicals, to increase the yields. The total amount of chemical fertiliser that was imported increased from about 1.3 million tonnes in 1985 to 3.9 million tonnes in 2004, with an annual growth rate of 4.6%. The value of imported chemical fertiliser also increased with a higher annual growth rate of 8.7%. The increasing use of chemical fertiliser and chemicals whose prices have been rising continuously has resulted in substantial increases in production costs. This paper aims to answer two questions: how has rural credit contributed to the production of rice? and how do agricultural loans from the rural financial institutions affect the technical efficiency of rice farmers? This study is based on data from farmers in Chiang Mai and Chiang Rai provinces which are the main areas for major rice production in the Upper North sub-region. The results from this study will be useful for determining the government policies on rural financial institutions. This paper is set out as follows: Sect. 2 provides an overview of the rural financial institutions. Section 3 presents survey data on rice farmers and model specifications. Section 4 discusses the results from the translog stochastic frontier production function. The last section provides policy implications and conclusions. ? 2009 Physica-Verlag Heidelberg.